2010
DOI: 10.1128/jvi.01815-09
|View full text |Cite
|
Sign up to set email alerts
|

NKp46 O-Glycan Sequences That Are Involved in the Interaction with Hemagglutinin Type 1 of Influenza Virus

Abstract: Natural killer (NK) cells serve as a crucial first-line defense against tumors and virus-infected cells. We previously showed that lysis of influenza virus (IV)-infected cells is mediated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 36 publications
(56 reference statements)
0
44
0
Order By: Relevance
“…This indicated that, similar to the binding of the influenza hemagglutinin lectin, NKp46 and NCR1 might bind to a lectin on the surface of Cg through the same sugar residue. The O-linked glycan on the NKp46/NCR1, Neu5Acα2-6 (Neu5Acα2-3Galβ1-3) GalNAc (Glasner et al, 2015; Mendelson et al, 2010), is shown in figure 3C. In Cg, the EPA genes encode a major family of glycan binding lectins, which mediate the attachment of the fungal cell to host cells.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that, similar to the binding of the influenza hemagglutinin lectin, NKp46 and NCR1 might bind to a lectin on the surface of Cg through the same sugar residue. The O-linked glycan on the NKp46/NCR1, Neu5Acα2-6 (Neu5Acα2-3Galβ1-3) GalNAc (Glasner et al, 2015; Mendelson et al, 2010), is shown in figure 3C. In Cg, the EPA genes encode a major family of glycan binding lectins, which mediate the attachment of the fungal cell to host cells.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we found that intrahepatic frequency of NKp46 High NK cells inversely correlated with HCV loads. Whether NKp46 recognizes a HCV-derived protein [17][18][19][20][21] or interacts with a yet unknown NKp46 ligand, as has been suggested for malignant transformed cells, 40,41 remains to be clarified. However, blocking of NKp46 significantly reduced the capability of both circulating and intrahepatic NK cells to block HCV replication, suggesting a role of NKp46 in the regulation of anti-HCV immune responses.…”
Section: Nk Cells (Supportingmentioning
confidence: 99%
“…Moreover, NKp46 plays an important role in the killing of virus-infected cells by interacting with viral proteins. [17][18][19][20][21] Studies on NKp46 in HCV infection are controversial, because both reduced and increased surface expression have been reported. 5,[7][8][9] In this context, it is of interest that earlier studies showed that the surface expression of NKp46 may vary in different human peripheral blood NK cells, and that the NKp46 phenotype of NK clones correlates with cytolytic activity.…”
mentioning
confidence: 99%
“…Early work showed that the viral hemagglutinin (HA) of influenza virus on the surface of infected cells can readily engage with branched α-2,3- and α-2,6-sialylated O -glycan sequences conjugated on NKp46, and influenza-infected target cells can be killed by human NK cells in a NKp46-dependent manner (6568). In fact, exposure of NK cells to influenza virions or free HA has been found to decrease NCR-mediated cytotoxicity, which was associated with loss of TCR-ζ protein expression (71).…”
Section: Ligands Of the Ncrsmentioning
confidence: 99%